Prediction of cellulolytic and hemicellulolytic bacterial diversity in the gut of Coptotermes gestroi in the Southern Vietnam - Thi Thao, Nguyen; Thi Huyen, Do; Nam Hai, Truong (Vietnam Journal of Biotechnology, 2020)
In lower termite such as Coptotermes gestroi, cellulose and hemicellulose are hydrolysed by cellulases and hemicellulases secreted from bacteria, archaea, protozoa and fungy in the hindgut. In which, majority of the enzymes are contributed by protozoa. From the metagenomic DNA data (125,423 open reading frames -ORFs) of free-living bacteria in the gut of C. gestroi harvested in Southern Vietnam and by MEGA 4.0 software, 100.340 ORFs were classified into 1,368 species, 628 genera, 217 families, 97 orders, 41 classes and 22 phyla (Do et al., 2014). Among these, 2,131 ORFs (2,12%) belong to 24 bacterial species (account 1,75% bacterial species), 11 families, 9 orders, 8 classes and 5 phyla were predicted have ability to produce cellulases; 679 ORFs belong to 18 bacterial species 8 families, 6 orders, 5 classes, 4 phyla were predicted have ability to produce hemicellulase. Majority of cellulase producers were species which of Firmicutes (15/24 species), accumulated in class Clostridia, order Clostridiales. The most abundant cellulase producer was Pseudomonas fluorescens (1,258 ORFs) of order Pseudomonadaceae. Out of the 18 hemicellulase producers, the most abundant species was Clostridium thermocellum (113 ORFs) in the phylum Firmicutes, followed by 3 species belonging to the phylum Bacteroidetes. The species predicted to produce both cellulase, hemicellulase were C. thermocellum, Ruminococcusns flavefaciens and Bacillus subtilis. Our study provides  a data of gut cellulose and hemicellulose - degrading bacteria composition of C. gestroi